(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
The article explores contemporary strategies for developing leadership competence in general education institutions. The research demonstrates that enhancing school leaders’ managerial, communicative, and innovative competencies is a critical factor in improving educational quality and institutional performance efficiency. It also addresses strategies for leadership competence development, the core meaning and content of the concept of competence, effective approaches targeted at leadership competence enhancement, and discusses the formation of leadership competence.